2020
DOI: 10.13057/biodiv/d211218
|View full text |Cite
|
Sign up to set email alerts
|

Biomass yield and growth allometry of some crops growing under weed stress

Abstract: Abstract. Qadir S, Khan A, Salam IU. 2020. Biomass yield and growth allometry of some crops growing under weed stress. Biodiversitas 21: 5621-5629. The conventional approach in crop science generally focuses on nutritional yield of crops. Crop yield is basically ranked by its photosynthetic efficiency. Hence the higher reserves of photosynthetic products are achieved in the form of biomass. Current study explains the gain and loss in biomass of five different crops viz, Zea mays L. (maize), Hordeum vulgare L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…These results illustrate that an increase in LAI is followed by an increase in WC, which will affect the resulting food reserves in the form of NAR. NAR describes the amount assimilated from photosynthesis that is stored in the form of food reserves in all plant organs (Qadir, Khan and Salam, 2020). Based on Table 2, showed that the use of rice husk produced the highest NAR followed by cow manure and rice straw compost, while green leaf compost and control produced a lower NAR.…”
Section: Resultsmentioning
confidence: 99%
“…These results illustrate that an increase in LAI is followed by an increase in WC, which will affect the resulting food reserves in the form of NAR. NAR describes the amount assimilated from photosynthesis that is stored in the form of food reserves in all plant organs (Qadir, Khan and Salam, 2020). Based on Table 2, showed that the use of rice husk produced the highest NAR followed by cow manure and rice straw compost, while green leaf compost and control produced a lower NAR.…”
Section: Resultsmentioning
confidence: 99%